Microwave radiation of the ocean-atmosphere : boundary heat and dynamic interaction /: boundary heat and dynamic interaction. ([2015]) - Grankov, A. G (Aleksandr Georgievich); Milʹshin, A. A (Aleksandr Alekseevich)
No abstract available